2007
DOI: 10.1007/bf03030664
|View full text |Cite
|
Sign up to set email alerts
|

CbLEA, a NovelLEA Gene fromChorispora bungeana, Confers Cold Tolerance in Transgenic Tobacco

Abstract: A novel late embryogenesis abundant (LEA) gene (AY804193), named CbLEA, has now been isolated from Chorispora bungeana. This rare alpine subnival plant can survive sudden snowstorms and low temperatures. The full-length CbLEA is 842 bp, with an open reading frame encoding 169 amino acids. The putative molecular weight of CbLEA protein is 17.9 kDa, with an estimated pl of 6.45. To investigate the functioning of this CbLEA protein in cold-stress tolerance, CbLEA was introduced into tobacco under the control of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…seed development (Bartels et al, 1988;Hartwigsen and Goggi, 2002). Their overexpression enhances tolerance to salt, drought, and osmotic stresses in transgenic plants (Brini et al, 2007;Zhang et al, 2007). Here, we observed that levels of OsALDH7 transcripts started to increase at the late stage of maturation, similar to those of the LEA genes.…”
Section: Discussionsupporting
confidence: 67%
“…seed development (Bartels et al, 1988;Hartwigsen and Goggi, 2002). Their overexpression enhances tolerance to salt, drought, and osmotic stresses in transgenic plants (Brini et al, 2007;Zhang et al, 2007). Here, we observed that levels of OsALDH7 transcripts started to increase at the late stage of maturation, similar to those of the LEA genes.…”
Section: Discussionsupporting
confidence: 67%
“…A late embryogenesis abundant (LEA) gene; CbLEA was isolated from Chorispora bungeana and introduced into tobacco whose overexpression exhibited cold tolerance by significantly higher RWC compared with their counterparts. The degree of chilling tolerance in tobacco was associated with high accumulation of CbLEA protein that protected the transgenic plants from cold injury (Zhang et al 2007). Yanez et al (2009) reported that bZIP transcription factor regulated cold inducible gene SlAREB1 and overexpression of this gene played an essential role in cold tolerance accumulating more RWC in Solanum genus.…”
Section: Discussionmentioning
confidence: 98%